Biopharmaceuticals. Official position of Russian Association of Endocrinologists - Editorial team Diabetes Mellitus (Сахарный диабет)
Some of the glucose-lowering drugs are biopharmaceuticals. This letter states the official position of the Russian Association of Endocrinologists about the treatment with biopharmaceuticals of patients with endocrine disorders. This topic has not yet beenadequately reflected in the legal regulation of the drug market in the Russian Federation .